Sociology of sport a global subdiscipline in review - Young, Kevin, 1959- (Bingley, U.K. : Emerald, 2016)
The Sociology of Sport has grown since its inception in the late 1950s and has become robust, and diverse. Many countries now boast strong scholars in the field and this volume reflects the fascinating research being done. This innovative volume is dedicated to a review of the state of the area by region, and country in some cases. For instance, Latin America is expanding widely in the field, and Korea and Japan have had vibrant Sociology of Sport communities for some time.
Sociology of sport: South Africa / Cora Burnett -- Sociology of sport: China / Jinxia Dong, Lingnan Liu -- Sociology of sport: India / Veena Mani, Mathangi Krishnamurthy -- Sociology of sport: Japan / Chiaki Okada, Kazuo Uchiumi -- Sociology of sport: South Korea / Eunha Koh -- Sociology of sport: Aotearoa/New Zealand and Australia / Chris Hallinan, Steven Jackson -- Sociology of sport: Czech Republic / Irena Slepickova<U+0301> -- Sociology of sport: Finland / Pasi Koski -- Sociology of sport: Flanders / Jasper Truyens, Marc Theeboom -- Sociology of sport: France / Ste<U+0301>phane He<U+0301>as, Patrice Re<U+0301>gnier -- Sociology of sport: Germany and Switzerland / Markus Lamprecht, Siegfried Nagel, Hanspeter Stamm -- Sociology of sport: Hungary / Tama<U+0301>s Do<U+0301>czi, Andrea Ga<U+0301>l -- Sociology of sport: Italy / Caterina Satta -- Sociology of sport: The Netherlands / Annelies Knoppers -- Sociology of sport: Norway, Sweden and Denmark / Jorid Hovden, Kolbjrn Rafoss -- Sociology of sport: Spain / Nu<U+0301>ria Puig, Anna Vilanova -- Sociology of sport: United Kingdom / John Horne, Dominic Malcolm -- Sociology of sport: Canada / Parissa Safai -- Sociology of sport: English-Speaking Caribbean / Roy McCree -- Sociology of sport: United States of America / Jeffrey Montez de Oca -- Sociology of sport: Argentina / Rau<U+0301>l Cadaa -- Sociology of sport: Brazil / Wanderley Marchi Ju<U+0301>nior -- Sociology of sport: Chile / Miguel Cornejo Amestica.
Includes bibliographical references.
Print version record
Keywords: Sports & Recreation -- Sociology of Sports; Sociology: sport & leisure; Sports -- Sociological aspects